PENGARUH KUALITAS PELAYANAN, KUALITAS PRODUK DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN PADA PDAM TIRTA RATU SAMBAN - Diah Dwi Artiza; Silvi Juwita (Yayasan Insani Mandiri Santani, 2021)
This study aimed to determine the effect of service quality, product quality, and satisfaction toward consumers’ loyalty at PDAM Tirta Ratu Samban branch of Hulu Palik sub-district, North Bengkulu. This research used a qualitative method. The sample of this research was 105 consumers of PDAM Tirta Ratu Samban branch of Hulu Palik sub-district, North Bengkulu that taken by using accidental sampling technique. The data was collected by using instruments such as observation and questionnaire. The data was analyzed by using multiple regression analysis and coefficient of determination. The results of the research show that Service Quality (X1), Product Quality (X2) and Consumers’ Satisfication (X3) have a simultaneous effect toward Customers’ Loyalty (Y) at PDAM Tirta Ratu Samban Branch Hulu Palik North Bengkulu. The results of regression equation analysis are as follows: Y = 0.689+ 0.237 (X_1) + 0.163 (X2) + 0.331 (X3). = 0.000 < 0.050), Product Quality, obtained tcount> ttable (3.284 > 1.98260) and (sig<α = 0.001<0.050), Consumers’ Satisfaction, obtained tcount>ttable (4.145 > 1.98260) and (sig<α = 0.000 < 0.050). This means that service quality, product quality, and consumers’ satisfaction have a significant effect on customer loyalty at PDAM Tirta Ratu Samban, Hulu Palik sub-district, North Bengkulu. Keywords: Service quality, product quality, consumers’ satisfaction, consumers’ loyalty